EVALUASI KEBIJAKAN REPRESENTATIF PEREMPUAN DI DEWAN PERWAKILAN RAKYAT DAERAH MANADO - MARAMIS, REGINA; LENGKONG, FLORENCE; LONDA, VERY (Sam Ratulangi University, 2020)
The purpose of this study is to determine the evaluation of women's representative policies in the ManadoRegional Representative Council. The research concept used in this study is to use a type of qualitativeresearch with a descriptive approach. Then the data collection technique is done by interview, observation,and documentation. Data analysis techniques in the study used qualitative data analysis of Miles andHuberman. The results showed that the evaluation of women's representative policies in the ManadoPeople's Representative Council was classified as good as seen from the number of women councilors whowere able to meet the regulations regarding a minimum of 30% involvement of women in parliament, but interms of the role of women councilors in determining and decision-making on unfinished policies. So it canbe concluded that the evaluation of women's representative policies in the Manado Regional RepresentativeCouncil has not been maximized in terms of the role of its female councilors.Keywords : Evaluation, Policy, Representative, Women